2010
DOI: 10.1152/ajpheart.00732.2009
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial flow induces MMP-1 expression and vascular SMC migration in collagen I gels via an ERK1/2-dependent and c-Jun-mediated mechanism

Abstract: The migration of vascular smooth muscle cells (SMCs) and fibroblasts into the intima after vascular injury is a central process in vascular lesion formation. The elevation of transmural interstitial flow is also observed after damage to the vascular endothelium. We have previously shown that interstitial flow upregulates matrix metalloproteinase-1 (MMP-1) expression, which in turn promotes SMC and fibroblast migration in collagen I gels. In this study, we investigated further the mechanism of flow-induced MMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 47 publications
4
68
0
1
Order By: Relevance
“…These stresses can be estimated by the hydraulic conductivity K of the interstitium (discussed in section IIID), since the latter is governed by the flow resistance of the solid phase of the material, i.e., the fluid-solid interactions in the pores or at the ECM fiber boundaries (487). In physiologically relevant interstitial flow rates, average shear stresses have been estimated at Ͻ0.1 dyn/cm 2 (423). These are much lower than those found in the blood vasculature, for example, but similar to shear stress estimates in lymph vessels (113,449).…”
Section: A Measurements Of If and Shear Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…These stresses can be estimated by the hydraulic conductivity K of the interstitium (discussed in section IIID), since the latter is governed by the flow resistance of the solid phase of the material, i.e., the fluid-solid interactions in the pores or at the ECM fiber boundaries (487). In physiologically relevant interstitial flow rates, average shear stresses have been estimated at Ͻ0.1 dyn/cm 2 (423). These are much lower than those found in the blood vasculature, for example, but similar to shear stress estimates in lymph vessels (113,449).…”
Section: A Measurements Of If and Shear Stressmentioning
confidence: 99%
“…Interestingly, it was found that superphysiological or pathological levels of interstitial flow, i.e., 3-10 m/s, could induce fibroblast motility through MMP-1 upregulation (423,424) as well as drive myofibroblast differentiation and matrix alignment (325-327) (FIGURE 15). This matrix alignment was more rapid (within 12-24 h after flow onset) than the myofibroblast differentiation (1-5 days).…”
Section: B Effects Of Interstitial Flow On Fibroblastic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…SS, shear stress; ASMC, aortic smooth muscle cell; TFPI-2, tissue factor pathway inhibitor-2; Dyn, dyn/cm 2 ; PDGF, platelet-derived growth factor; MMP, matrix metalloprotease; HO, haem oxygenase; CO, carbon monoxide; NO, nitric oxide; ERK1/2, extracellular signal-regulated kinase1/2; AKT, protein kinase B; min, minute (or minutes); h, hour (or hours); d, day (or days [17] laminar SS 6 dyn bovine ASMC aligned along the direction of SS [18] physiological SS 12 dyn rat ASMC NO at 12 -24 h SS-suppressed proliferation and migration [19] laminar SS 3, 6 and 9 dyn bovine ASMC high SS inhibits SMC proliferation [20] rsif.royalsocietypublishing.org J. R. Soc. Interface 11: 20130852 c-Jun-mediated signalling [54,56]. The mechanotransduction can be transmitted by HSPGs and ERK1/2 [41].…”
Section: Haemodynamic Factors and Vascular Smoothmentioning
confidence: 99%
“…When compared with smooth muscle cells (SMCs) from normal veins, SMCs from VVs are more dedifferentiated and show increased migration, proliferation, and MMP-2 production, which may contribute to vein wall remodeling and weakening against increased hydrostatic pressure (Xiao et al, 2009). MMP-1 and -9 levels have also been shown to increase human aortic SMC migration (Jin et al, 2008;Shi et al, 2010). MMP-induced ECM proteolysis may modulate cell-matrix adhesion either by removal of sites of adhesion or by exposing a binding site and, in turn, facilitate VSMC migration.…”
Section: Mmps and Vsm Dysfunction In Vvsmentioning
confidence: 99%